Indirect detection of multi-wave length for infrared wireless communications in the room and public area services - Sudkaew, S.; Sartthong, J.; Noppanakeepong, S.; Manyanon, A. (My University, 2003)
In this paper, optical multi-wavelength modulation is proposed to reduce the effects of intersymbol interference (ISI) on the artificial light noise and multi path channels. The noise model in the room is the Additive White Gaussian Noise (AWGN), and multi wavelength optical modulation schemes are used for On Off Keying (OOK). An infrareds link in the room or public area services used Intensity Modulation and Direct Detection ( MD ). The normal room and some interior in this case are used to study the obstruction and the reflex effect to the communications speed rate at 10-100Mbps. Finally each performance of BER per Transmitted light power of Multi-wavelength Infiared system is compared. The carrier characteristic of Multi-wavelength wiIl be improved to be same as RF- carriers on mobiles applications.
Keywords: ISI; Multi wavelength; OOK.IM/DD